STUDI ANALISIS PENENTUAN JUMLAH MAHAR OLEH TOKOH ADAT PERSPEKTIF HUKUM ISLAM - Mahmudi, Muhammad Salim; Sabri, Yuli; Ikhsan, Ikhsan; Jani, Rafsan; Amiruddin, Amiruddin (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The determination of the amount of dowry by traditional leaders often faces challenges between local traditions and Islamic teachings. On the one hand, traditional leaders play an important role in maintaining the continuity of long-standing cultural values, taking into account the social status, economic status of the family, and local customs. However, on the other hand, Islamic law teaches that dowry must be simple, fair, and in accordance with the man's ability, without any element of coercion or undue burden. This research uses a library research approach, which focuses on the study of literature that is relevant to the topic. The main source of data in this study comes from scientific journal articles, books that discuss Islamic law, marriage fiqh, and customs related to dowry and published research reports. The results of the study show that: 1). The method of determining the amount of dowry carried out by traditional leaders is that the determination of the amount of dowry by traditional leaders is generally carried out through deliberation between the two parties of the family, taking into account the economic ability of the male family and local customary traditions. 2). The factors that affect the decision of traditional leaders in determining the amount of dowry are that the decision of traditional leaders in determining the amount of dowry is influenced by several main factors, namely the social status of the family, the economic condition of the male family, and the prevailing customary norms. 3). The determination of the amount of dowry made by traditional leaders according to Islamic law is that in the perspective of Islamic law, dowry should be determined based on the financial ability of the man's family and given in good faith as the right of the bride.